Random access at double the speed. - Geppert, N.
Unveiled at the IEEE's Symposium on VLSI Circuits, a novel dynamic memory architecture challenges static memory.
Keywords: 512 Kbit; ASIC; IBM demonstration chip; Architectural device; Circuit blocks; Dynamic memory architecture; Embedded DRAM; Macros; On-chip memory applications; Systems-on-chip.; Write-back buffer